Biogas Fed-fuel Cell Based Electricity Generation: A Life Cycle Assessment Approach - Shafie, S. M.; Othman, Z.; Hami, N.; Omar, S.; Nu'man, A. H.; Yusoff, N. N.A.N.; Shaf, A. (International Journal of Energy Economics and Policy, 2020)
The world is currently facing a scarcity of energy resources in the electricity generation sector. The current pattern of electricity generation has brought harm to the environment. Fuel cell provides a huge potential in reducing the negative environmental impacts. Malaysia as a tropical country has abundant sources of biogas production that can be fed into the fuel to produce electricity and water. The paper aimed to identify the environmental impact towards the consumption of biogas feeding into fuel cells for electricity generation. The result showed that in this modelling of system boundary, the greenhouse gas (GHG) emissions were high due to large contributions from the transportation and storage processes. Hopefully, the outcome from this study could help future researchers or stakeholders in making decisions to design fuel cells for electricity generation with minimum environmental impact contribution. Keywords: Biogas, fuel cell, electricity generation, LCA, sustainability JEL Classifications: C32; O13; O47 DOI: https://doi.org/10.32479/ijeep.9957